Attiring Business for Success and Enjoyable Involvements of Customers’ Interface with VM Essentials: The Role of Visual Merchandising in Enhancing Customer Engagement and Marketing Success (Journal of Advances and Scholarly Researches in Allied Education, 2013)
An imperative marketing gizmo accessible with marketers is visual merchandising which is acclaimed as a catalyst to entice the consumer towards the product and at the same time fashioning its image which helps in extricating distinctly its charisma in comparison to competitor’s products. Visual Merchandising bounces a communication from retailers to its customer vis-à-vis the merchandise it commends. Visual Merchandising is a fundamentally exploited custom of trade appropriate as per the rudiments of the structured retailers stipulating the engrossment of the customer in the involvement of buying innumerable products and stimulus instantaneous purchases. Visual Merchandising is expended as a constituent of consistency and modifications in the retail industry. To concoct a swift pronouncement of procurement it grinds on catechizing the customers. To assimilate the acquaintance of Visual Merchandising and engendering an underlying instrument for imminent marketing espousal in the context of organized merchandising is the intention of this paper.